Social Media & Young Generation Participation on Electoral Vote - Haque, Shaha; Liza, Sharmin (oneamd.com, 2024)
It is expected that over the top utilization of social media among youthful eras, i.e., understudies of colleges make them more socially coordinates and politically educated. Political parties utilize media as well as social media to representation candidates and their different issues which pull in mass individuals. In spite of the fact that there are a few ponders around, which approves these impact of social media on cooperation of youthful era in discretionary legislative issues is done already for a few nations of world but however, for the nation Bangladesh, there's no such consider still existing which uncovers these issues with explanatory-descriptive investigation, especially done for any specialized open college, where web is more reasonable than to other sorts of colleges, since of the extra consideration is given to data and communications innovation there. Blended strategy has been connected to create the ponder more solid. The ponder here maybe is done with a organize of organized survey and Center Gather Discourse; basic irregular inspecting and cluster testing to fulfill the subsisting crevice in this way have found the foremost common sorts of websites utilized by respondents, normal term of them in day by day premise, whether on other hand, have evaluated that adequacy of social media to motivate youthful era in political cooperation.